Preparation, characterization, and application of vertically aligned CNT sheets through template assisted pyrolysis of PBI‐Kapton. (1st November 2016) - Azami, Hamed; Omidkhah, Mohammad Reza
Abstract : This article investigates the synthesis of vertically aligned carbon nanotube (CNT) sheets through the pyrolysis of polybenzimidazole (PBI)‐Kapton inside the pores of anodized aluminium oxide (AAO). The nanocomposites of CNT/Alumina obtained were characterized by several techniques. It was found that the resulting carbon structures presented higher crystallinity compared with graphite. All of the CNT sheets had high antibacterial activity that was proportional to degree of CNT crystallinity. Moreover, the desalination of salty water using CNT sheets was performed. The results demonstrated that the vertically aligned CNT sheets could be used as an effective adsorbent for salty water desalination due to their very high adsorption capacity without CNT leakage into water. Abstract : The synthesis of antibacterial vertically aligned CNT sheets through template‐assisted pyrolysis of PBI‐Kapton.